Potential for Isolation of Immortalized Hepatocyte Cell Lines by Liver-Directed In Vivo Gene Delivery of Transposons in Mice - Masahiro Sato; Issei Saitoh; Emi Inada; Shingo Nakamura; Satoshi Watanabe (Stem Cells International)
Isolation of hepatocytes and their culture in vitro represent important avenues to explore the function of such cells. However, these studies are often difficult to perform because of the inability of hepatocytes to proliferate in vitro. Immortalization of isolated hepatocytes is thus an important step toward continuous in vitro culture. For cellular immortalization, integration of relevant genes into the host chromosomes is a prerequisite. Transposons, which are mobile genetic elements, are known to facilitate integration of genes of interest (GOI) into chromosomes in vitro and in vivo. Here, we proposed that a combination of transposon- and liver-directed introduction of nucleic acids may confer acquisition of unlimited cellular proliferative potential on hepatocytes, enabling the possible isolation of immortalized hepatocyte cell lines, which has often failed using more traditional immortalization methods.